Meta-Analysis of HER2-Enriched Subtype Predicting the Pathological Complete Response Within HER2-Positive Breast Cancer in Patients Who Received Neoadjuvant Treatment - Shen, Guoshuang; Zhao, Fuxing; Huo, Xingfa; Ren, Dengfeng; Du, Feng; Zheng, Fangchao; Zhao, Jiuda (Frontiers in Oncology, 2021)
Background: This meta-analysis aimed to better elucidate the predictive value of human epidermal growth factor receptor 2 (HER2)-enriched subtype of pathological complete response (pCR) rate within HER2-positive breast cancer patients receiving neoadjuvant treatment. Methods: We identified prospective trials that evaluated the correlation between an HER2-enriched subtype and pCR rate in HER2-positive breast cancer. Pooled odds ratio (OR) values with 95% confidence intervals (CIs) were computed. Results: Fifteen studies comprising 2,190 patients met the inclusion criteria. The HER2-enriched subtype was associated with increased odds of achieving a pCR (OR = 4.12, 95% CI = 3.38 to 5.03, P < 0.001) in patients overall. Moreover, it was correlated with improved pCR when single or dual HER2-targeted agent-based therapy was employed (OR = 3.36, 95% CI = 2.25 to 5.02, P < 0.001; OR = 4.66, 95% CI = 3.56 to 6.10, P < 0.001, respectively), but not when HER2-targeted agent-free chemotherapy was used (OR = 2.52, 95% CI = 0.98 to 6.49, P = 0.05). Moreover, an HER2-enriched subtype predicted higher pCR rates irrespective of HER2-targeted agents (trastuzumab, lapatinib, pertuzumab, or T-DM1); chemotherapy agents (taxanes-based, or anthracyclines plus taxanes-based); endocrine therapy and hormone receptor (all the difference was statistically significant (P all ≤ 0.001)). Conclusions: The HER2-enriched subtype can more effectively and specifically predict pCR for HER2-targeted agent-based neoadjuvant treatment, irrespective of the number (single or dual) or category of HER2-targeted agent, including chemotherapy and endocrine therapy, or hormone receptor in cases of HER2-positive breast cancer.